(untitled) (Global Scientific Review, 2025)
This article reveals the ethical aspects of virtual science. Virtual culture among young people in the information society is scientifically informed about its impact on social life. Today’s views on social life, that is, on virtual society, virtual realities and their influence on today’s social processes are widely explained